Analysis on the Structural Transformation of ITER TF Conductor Jacket Tube1. Issue 3 (30th April 2014) - Yang, Huihui; Huang, Chuanjun; Wu, Zhixiong; Huang, Rongjin; Li, Laifeng
Abstract : For ITER TF jacket tube, induced γ‐α′ phase change is related to both temperature and structure deformation, decreasing temperature less external energy is needed. The maximum phase change is occurred at fracture, a gradual transformation occurs parallel the longitudinal direction. Particularly, α′ phase is prone to form at the boundaries of initial austenite grains, uniformly dispersed in the austenite structure.